Production of polyclonal antibodies against the DJ-1 protein associated with Parkinson's disease - Mussakhmetov, A.; Baltin , K.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2022)
Parkinson's disease is a slowly progressive chronic neurodegenerative disease with a global prevalence estimated at 0.3% and rising sharply with age to over 3% in people over 80 years of age. Estimates of the incidence of Parkinson's disease worldwide range from 5 to 35 new cases per 100,000 people per year. The disorder is defined by the presence of classic motor signs, including the characteristic presence of bradykinesia in all patients, tremor in most, and rigidity. One of the proteins associated with Parkinson's disease is DJ-1, also known as Parkinson disease protein 7 (PARK7). Studies have shown that DJ-1 is an antioxidant protein that plays a key role in counteracting oxidative stress in dopamine neurons. In the framework of the studies carried out in Escherichia coli BL21(DE3)-RIPL strain, the recombinant rDJ-1 protein was obtained in an amount of 3.5 mg. By immunizing a rabbit, polyclonal anti-rDJ-1 antibodies were isolated, which, in enzyme immunoassay and Western blotting, showed high sensitivity to the DJ-1 protein at a dilution of up to 1: 512,000. The resulting polyclonal antibodies showed the required informativeness when studying the expression of DJ-1 in the cell lines HEK293 (wild type) and HEK293park- (with knocked-out park gene). The resulting antibodies can be used in studies to assess the expression level of DJ-1 in immunological tests to detect and quantify the target protein: flow cytometry, ELISA, Western blotting, immunofluorescence, immunohistochemistry, immunoelectrophoresis.